Penilaian Kualitas Air Sungai Dan Potensi Pemanfaatannya Studi Kasus S. Cimanuk - Armaita Sutriati (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2011)
Cimanuk is one of considerable potential river in West Java besides the Citarum River and Citanduy. Associated with the use of river water as raw water Cimanuk for various uses, needs to be monitoring thewater quality conditions continuously. Cimanuk water quality assessment conducted to determine compliance with its allocation, state of water quality status and trends of water quality changes from time to time. The research method involves sampling, measurement of field parameters, testing the water quality in the laboratory, evaluation and assessment of water quality conditions. Based on water quality data during the period of years 20052009, showed that the characteristic Cimanuk water quality is better. This can be seen from the level of freshness still meet water quality criteria with dissolved oxygen content greater than 3 mg/L. Potential of Cimanuk water quality in the rainy season is the Class I of Government Regulation no. 82/2001 (water that can be used for various uses), Class III and Class IV i n the dry season. Assessment of water quality status were calculated using STORET method. If the assessment carried out on B,C,D Class ofState Java Governor no. 38/1991, Cimanuk River conditions are